2007
DOI: 10.1103/physrevc.75.044307
|View full text |Cite
|
Sign up to set email alerts
|

Chiral bands for a quasi-proton and quasi-neutron coupled with a triaxial rotor

Abstract: A particle rotor model (PRM) with a quasi-proton and a quasi-neutron coupled with a triaxial rotor is developed and applied to study chiral doublet bands with configurations of a h 11/2 proton and a h 11/2 quasi-neutron. With pairing treated by the BCS approximation, the present quasiparticle PRM is aimed at simulating one proton and many neutron holes coupled with a triaxial rotor. After a detailed analysis of the angular momentum orientations, energy separation between the partner bands, and behavior of elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
124
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 43 publications
5
124
0
Order By: Relevance
“…It shows that the time-odd fields may reduce the triaxial deformation parameter γ by 0.5 • . Using the structure information for the configuration νh 1 11/2 ⊗ πg −3 9/2 as inputs in a triaxial rotor coupled with the quasiparticle model [14,15], the energy spectra and the electromagnetic transition ratios for a pair of negative-parity doublet bands in 106 Rh are well reproduced in Ref. [29].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It shows that the time-odd fields may reduce the triaxial deformation parameter γ by 0.5 • . Using the structure information for the configuration νh 1 11/2 ⊗ πg −3 9/2 as inputs in a triaxial rotor coupled with the quasiparticle model [14,15], the energy spectra and the electromagnetic transition ratios for a pair of negative-parity doublet bands in 106 Rh are well reproduced in Ref. [29].…”
mentioning
confidence: 99%
“…Later on, numerous efforts were devoted to the development of TAC methods [8][9][10][11] and PRM models [12][13][14][15] to describe chiral rotation in atomic nuclei. It is shown that triaxial deformation and high-j valence particles and valence holes are essential for the formation of chirality in nuclei.…”
mentioning
confidence: 99%
“…For all the PRM calculations, the πh 11/2 ⊗ νh −1 30 For the electromagnetic transitions, the intrinsic quadrupole moment Q 0 takes an empirical value of 3.5 eb and the gyromagnetic ratios g R = Z/A ≈ 0.44, and g p = 1.21, g n = −0.21 are adopted in the A ∼ 130 mass region. 31,32 The level scheme of doublet bands can be organized from the calculated results of PRM. For an ideal case, the πh 11/2 ⊗νh −1 11/2 configuration with γ = 30 • , the levels of the two bands cross each other at certain spins.…”
Section: Resultsmentioning
confidence: 99%
“…Various models have been developed to study the nuclei in the transitional region, among which the triaxial particle-rotor model (PRM) [13][14][15] is widely applied to investigate the properties of rotational bands. 034303-4 TABLE I. γ -ray transition energies (uncertainties of 0.1-0.5 keV), initial and final level energies, spin-parity assignments, relative γ -ray intensities (uncertainties of 5-30%, and normalized to the 455.8-keV transition), and DCO ratios in 189 Pt.…”
Section: Theoretical Calculationsmentioning
confidence: 99%